The Heroine Concept in a Filipino Graphic Narrative - Arroyo, Estrella T. (Universitas Ahmad Dahlan, 2021)
This study explored the concept of â€œHEROINEâ€ in the context of â€œDarna,â€ a Filipino graphic narrative written by Mars Ravelo that was first published on May 13, 1950 by Filipino Komiks. Extracted from the 27 episodes of â€œDarnaâ€ are realities of experience as well as innuendos related to the real character of Darna, the super heroine. Further, the study delved into a deeper meaning of heroine beyond its lexical meaning. As a result, the researcher formulated her own definition of â€œHEROINEâ€ as â€œHumaneness and Equanimity in Reimagining Optimistic, Iconic, Novel, and Empoweredâ€ persona, which led to the findings that, indeed, Darna has reached her apotheosis as a superheroine. These insights were not fathomed had it not been for the researcherâ€™s focus on close reading, application of Expressive Realism, and â€œArgusticâ€ reading. Keen eyes are needed to enjoy reading a graphic narrative which is both visual and verbal. The study proved that in Philippine society, Darna is the most accepted, loved and idolized Filipino icon as savior of a devastated and crippled society after World War II. Lastly, it is aimed that this humble analysis will put itself into the realm of a body of Pop Literature and the Humanities.Â